Proposing models of Unit Trust Waqf - Sulaiman, Syahnaz; Hasan, Aznan; Mohd Noor, Azman (Emerald Publishing, 2019)
This paper aims to present the viability of unit trust waqf as an alternative asset class for waqf creation. The paper provides the conceptual framework of four models of unit trust waqf and their investment management parameters. This paper starts with the conceptual exploration of the literature in the area of waqf, which are sourced from authentic sources of Al-Quran and Al-Hadith, as well as secondary sources such as books, journal articles and online resources. The novelty of this paper lies in its attempt to highlight the importance of waqf investment strategy in ensuring sustainable return for waqf, by introducing the conceptual models for unit trust waqf as the viable mechanisms to pool more cash waqf from individual investors. The sustainability of the capital waqf assets in the form of unit trust is preserved through the parameters for its application as proposed toward the end of the paper